A metal double-coated tough gradient polycrystalline diamond compact and a preparation method thereof

CN118493963BActive Publication Date: 2026-11-03CHINA UNIV OF GEOSCIENCES (BEIJING) +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310114463.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2026-11-03
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

Existing polycrystalline diamond composite (PDC) sheets are prone to diamond layer detachment during long-term radial load application, exhibit poor thermal stability, and are prone to graphitization in high-temperature environments, resulting in insufficient wear resistance and impact resistance.

Method used

A strong and tough gradient polycrystalline diamond composite sheet with dual metal coatings is adopted. By setting bumps and grooves to limit the connection between the tungsten carbide alloy substrate layer and the uncoated diamond layer, and magnetron sputtering is performed on the surface of the diamond layer to form a multi-layer gradient structure, which enhances the interlayer connection strength and thermal stability.

Benefits of technology

It effectively prevents the diamond layer from delaminating with the alloy substrate, improves oxidation resistance and graphitization resistance, enhances the toughness of the composite sheet, makes it adaptable to high-speed and high-impact working conditions, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118493963B_ABST
    Figure CN118493963B_ABST
Patent Text Reader

Abstract

The present application relates to superhard material and hard material technical field, and disclose a kind of metal double plating layer strong tough gradient type polycrystalline diamond compact, including tungsten carbide alloy base layer, the top of the tungsten carbide alloy base layer is fixed with no plating diamond layer by boss and groove limiting mode, the boss and groove limiting mode has two, the top of the no plating diamond layer is fixed with plating diamond and no plating diamond mixed layer, the top of the plating diamond and no plating diamond mixed layer is fixed with plating metal diamond layer.The metal double plating layer strong tough gradient type polycrystalline diamond compact and its preparation method, by the two kinds of limiting connection mode between no plating diamond layer 3 of tungsten carbide alloy base layer 4, diamond layer and alloy base layer can withstand greater radial load, effectively prevent the phenomenon that fault occurs between diamond layer and alloy base layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhard materials technology, specifically to a metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method. Background Technology

[0002] Polycrystalline diamond composite (PDC) is a novel functional material made by sintering diamond micropowder with a cemented carbide substrate under ultra-high pressure and high temperature conditions. It combines the high hardness, high wear resistance, and thermal conductivity of diamond with the strength and impact toughness of cemented carbide, making it an ideal material for manufacturing cutting tools, drilling bits, and other wear-resistant tools. It is widely used in geological drilling, machining, gem processing, and unconventional oil and gas exploration. Due to its inherent advantages, PDC is being researched and produced both domestically and internationally, with a wide variety of specifications available. The preparation method of PDC determines its product quality and is of vital importance for designing and manufacturing long-life cutting and drilling equipment and promoting its application in major drilling projects.

[0003] However, existing PDCs are prone to diamond (PCD) layer detachment during long-term radial load application, and their thermal stability is poor in high-temperature environments. For example, they have low oxidation temperature, are prone to graphitization, suffer from thermal damage cracks leading to poor wear resistance, and are susceptible to adverse factors introduced by the cobalt metal catalyst. These limitations of PDCs are becoming increasingly apparent. Therefore, there is a need to provide a PDC with a longer service life, good impact resistance and thermal stability, which can not only have good fracture toughness, but also delay the oxidation and graphitization of PCD, so as to reduce the limitations of PDC applications. Summary of the Invention

[0004] (a) Technical problems to be solved

[0005] To address the shortcomings of existing technologies, this invention provides a metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method, thereby solving the problems of PDC being easily broken, not resistant to high temperatures, easily graphitized, and having poor impact performance.

[0006] (II) Technical Solution

[0007] To achieve the above-mentioned goals of solving the problems of PDC's easy breakage, poor high-temperature resistance, easy graphitization, and poor impact performance, the present invention provides the following technical solution: a metal double-coated tough gradient polycrystalline diamond composite sheet, comprising a tungsten carbide alloy substrate layer, wherein an uncoated diamond layer is fixed on the top of the tungsten carbide alloy substrate layer by means of protrusions and grooves, wherein there are two ways of protrusions and grooves for limiting the diamond layer; a mixed layer of coated diamond and uncoated diamond is fixed on the top of the uncoated diamond layer; and a coated metal diamond layer is fixed on the top of the mixed layer of coated diamond and uncoated diamond.

[0008] 2. A metal double-coated, high-strength gradient polycrystalline diamond composite sheet and its preparation method, comprising the following steps:

[0009] 1) Preparation of micro powders for each layer of the composite sheet;

[0010] Micronized powder cleaning: After acid washing and alkali washing of three different sizes of diamond micronized powder, rinse with distilled water 2-3 times;

[0011] Micronized powder coating: The cleaned diamond micronized powder is placed in a magnetron sputtering coating equipment, and two or three different particle sizes of diamond micronized powder from targets with a purity higher than 99.99% are deposited and coated on the surface.

[0012] Obtaining the mixture: A mixture is obtained by grinding cobalt powder and one of the whiskers as sintering agents, whisker balls and coated diamond micro powder.

[0013] Thoroughly mix the materials: The obtained mixture is thoroughly stirred and mixed in a vacuum environment using a planetary mixer equipped with a vacuum mixing tank.

[0014] 2) Obtaining the billet:

[0015] Particle Laying: Take a metal mold cup, mix tungsten carbide powder with a small amount of cobalt powder thoroughly and evenly, and lay it on the inner bottom wall of the metal mold cup as a tungsten carbide alloy base layer. Then, lay a metal mold sheet on top of the tungsten carbide alloy base layer. Next, lay a layer of uncoated diamond micro powder on top of the metal mold sheet as an uncoated diamond layer. Then, lay a thoroughly mixed layer of uncoated diamond micro powder and metal double-coated diamond micro powder on top of the uncoated diamond layer as an uncoated diamond mixed layer. Finally, lay ruthenium-tantalum double-coated diamond micro powder that has undergone two magnetron sputtering coatings as a coated metal diamond layer.

[0016] Pressing the blanks: Place the bottom of the metal mold cup on the top of the pyrophyllite sheet, and fit the top of the metal mold cup inside the pyrophyllite block, so that the metal mold cup is placed inside the cavity formed by the pyrophyllite block and the pyrophyllite sheet. Place the device on a column press and press it into blanks with hydraulic pressure of 25-35MPa.

[0017] 3) Obtain the finished product:

[0018] Blank reduction treatment: Take out the pressed blanks one by one and place them in the cavity of the graphite assembly in the order of pressing the blanks. Reduce the blanks in a vacuum environment for 24 hours. The graphite assembly includes a graphite tube, which is sleeved on the side of the blank. Graphite sheets are tightly attached to the top and bottom of the graphite tube.

[0019] High-temperature and high-pressure sintering of billet: The reduced billet, together with the graphite component, is placed in the sintering component and sintered into a polycrystalline diamond composite sheet under high temperature and high pressure using a six-sided press. The sintering component includes two phosphor iron sheets, which are tightly attached to the top and bottom of the two graphite sheets respectively. Composite conductive plugs are tightly attached to the top and bottom of the two phosphor iron sheets respectively. A dolomite tube is sleeved on the side of the graphite tube, and a second pyrophyllite block is sleeved on the outside of the dolomite tube and the composite conductive plug.

[0020] Finished product: The final product is obtained through ball milling, acid washing, and polishing.

[0021] Preferably, the whiskers in step 1) include silicon nitride whiskers, aluminum nitride whiskers, boron nitride whiskers and zirconium oxide whiskers, wherein the boron nitride whiskers have a length of 30-50 μm and a diameter of 3-5 μm, and the cobalt powder has an average particle size of 10-30 μm and a density of 8.9 g / cm3.

[0022] Preferably, the three different particle sizes of the diamond micro powder in step 1) are 1-2μm, 4-8μm, and 30-50μm, respectively.

[0023] Preferably, in step (1), the acid washing and alkaline washing are performed by boiling the diamond micro powder for 30 minutes with 10 wt.% NaOH and 30 wt.% HNO3 solutions, respectively.

[0024] Preferably, in the mixture obtained in step 1), the mass percentage of cobalt is 5-10 wt.%, the mass percentage of whiskers is 1-5 wt.%, and the mass percentage of diamond is 85-90 wt.%.

[0025] Preferably, in step 1), the thickness of the metal double coating is not the same, and for diamond micro powder with particle sizes of 1-2μm, 4-8μm, and 30-50μm, the corresponding total coating thicknesses are 0.10-0.15μm, 0.2-0.3μm, and 0.3-0.5μm, respectively. The diamond powder is prepared by magnetron sputtering, and the target material is selected from two or three of the following high-purity metals: ruthenium, tantalum, niobium, hafnium, technetium, scandium, and vanadium. The chamber vacuum is 5×10-3Pa, the sputtering power is 120-180W, the target current is 0.5A, and the working pressure is 0.4Pa. In order to make the diamond powder coating as uniform as possible, the sample stage is continuously oscillated during the coating process. For diamond micro powder with particle sizes of 1-2μm, 4-8μm, and 30-50μm, the corresponding total sputtering times are 15min, 30min, and 60min, respectively.

[0026] Preferably, in step 1), the mixture contains 5-10 wt.% diamond powder with a particle size of 1-2 μm, 10-15 wt.% diamond powder with a particle size of 2-4 μm, and 75-85 wt.% diamond powder with a particle size of 30-50 μm.

[0027] Preferably, the tungsten carbide powder in step 1) has a Co content of 16 wt.%.

[0028] Preferably, in step 1), the high-temperature and high-pressure pressure of the six-sided top press is 55-60 MPa oil pressure, the temperature is 1450-1600℃, and the sintering time is 5-15 min.

[0029] Preferably, the polishing method in step 1) is laser polishing, with a laser power of 6-10MW, a scanning speed of 1000μm / s, and a scanning spacing of 10-15μm.

[0030] (III) Beneficial Effects

[0031] Compared with the prior art, the present invention provides a metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method, which has the following beneficial effects:

[0032] 1. The metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method, through two limiting connection methods between the tungsten carbide alloy substrate 4 and the uncoated diamond layer 3, enable the diamond layer and the alloy substrate to withstand greater radial loads and effectively prevent the phenomenon of discontinuity between the diamond layer and the alloy substrate.

[0033] 2. The metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method, by treating the microparticles laid in each layer in different ways, effectively improves the oxidation resistance and graphitization resistance of the composite sheet. Furthermore, by optimizing the microparticles in each layer of the composite sheet, the toughness of the composite sheet can be optimized, making the composite sheet made in this way suitable for high-speed and high-impact working conditions, reducing the limitations of the composite sheet in use, and improving the service life of the composite sheet. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of a metal double-coated tough gradient polycrystalline diamond composite sheet structure proposed in this invention.

[0035] Figure 2 This is a schematic diagram of the structure of a metal double-coated tough gradient polycrystalline diamond composite sheet at the graphite sheet proposed in this invention.

[0036] Figure 3 This is a schematic cross-sectional view of the second pyrophyllite block of a metal double-coated tough gradient polycrystalline diamond composite sheet proposed in this invention.

[0037] Figure 4 This is a schematic diagram of two connection methods at the tungsten carbide alloy substrate layer of a metal double-coated tough gradient polycrystalline diamond composite sheet proposed in this invention.

[0038] In the diagram: 1. Coated metal diamond layer; 2. Mixed layer of coated diamond and uncoated diamond; 3. Uncoated diamond layer; 4. Tungsten carbide alloy substrate layer; 5. Pyrophyllite block; 6. Metal mold cup; 7. Pyrophyllite sheet; 8. Second pyrophyllite block; 9. Dolomite tube; 10. Graphite sheet; 11. Composite conductive plug; 12. Phosphorus iron sheet; 13. Graphite tube. Detailed Implementation

[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Please see Figure 1-4 A metal double-coated tough gradient polycrystalline diamond composite sheet and its preparation method;

[0041] Example 1:

[0042] A boron-titanium double-coated polycrystalline diamond composite sheet was prepared by first performing magnetron sputtering coating on diamond micropowder. Before the experiment, the diamond micropowder was boiled for 30 minutes in 10 wt.% NaOH and 30 wt.% HNO3 solutions, and then cleaned with distilled water 2-3 times for surface purification. 15g of diamond micropowder with a particle size of 1-2μm was placed in a magnetron sputtering coating apparatus. The chamber was evacuated to approximately 4×10⁻³ Pa. A ruthenium target with a purity higher than 99.99% was used. The sputtering power was 150W, the target current was 0.5A, and the working pressure was 0.5Pa. Ruthenium plating was performed on the surface of diamond micropowder under a 30-minute spraying time. Subsequently, tantalum plating was performed on the surface of the diamond micropowder using a tantalum target under the same conditions. During the plating process, the chamber temperature was maintained at room temperature, and the diamond disk was ultrasonically vibrated to continuously tumble the diamond, achieving uniform and seamless plating of the powder. The plating thickness was 0.1-0.15 μm. The same mass of diamond micropowder with particle sizes of 4-8 μm and 30-50 μm was then used to repeat the above operation, with plating thicknesses of 0.2-0.3 μm and 0.3-0.5 μm, respectively. Finally, the three types of coated diamond micropowder were thoroughly mixed.

[0043] like Figure 1 and Figure 2As shown, during assembly, tungsten carbide powder is first thoroughly mixed with a small amount of cobalt powder, and then evenly spread in a metal mold cup 6. This layer is the tungsten carbide alloy base layer 4. A metal mold sheet is then placed on top, followed by a layer of uncoated diamond micro powder 3 on the mold. The next step is to spread a thoroughly mixed layer of uncoated diamond micro powder and metal double-coated diamond micro powder 2. Finally, a layer of ruthenium-tantalum double-coated diamond micro powder 1, which has undergone two magnetron sputtering coatings, is spread on top. The mold is then placed into a cavity composed of pyrophyllite blocks 5 and pyrophyllite sheets 7, and pressed into a blank on a column press. After removal, the blank is placed in a graphite mold and subjected to vacuum reduction treatment for 24 hours. The graphite assembly block is then placed back into the pyrophyllite block and assembled in a six-sided top press. The assembly method is as follows. Figure 3 As shown, the sintering oil pressure is 55-60 MPa, the temperature is 1450-1600℃, and the temperature is maintained for 10 minutes after heating. Finally, the processed polycrystalline diamond composite sheet is subjected to ball milling and acid washing to remove the cemented carbide particles mixed in the surface.

[0044] Example 2:

[0045] Before the experiment, the diamond micropowder was boiled for 30 minutes in 10 wt.% NaOH and 30 wt.% HNO3 solutions, and then cleaned 2-3 times with distilled water. 15g of diamond micropowder was placed in a magnetron sputtering coating apparatus, and the chamber was evacuated to approximately 5 × 10⁻³ Pa. A niobium target with a purity higher than 99.99% was used, and the diamond micropowder was sputtered under the following conditions: sputtering power of 150W, target current of 0.5A, working pressure of 0.5 Pa, and sputtering time of 30 minutes. A niobium layer was deposited on the surface of the diamond micropowder, followed by scandium deposition on the surface of the diamond micropowder using a scandium target under the same process conditions. During the deposition process, the chamber temperature was maintained at room temperature, and the diamond disk was subjected to ultrasonic vibration to continuously tumble the diamond, achieving uniform and seamless deposition of the powder. The coating thickness was 0.15 μm. Subsequently, the same mass of diamond micropowder with particle sizes of 4-8 μm and 30-50 μm was used to repeat the above operation, with coating thicknesses of 0.2-0.3 μm and 0.3-0.5 μm, respectively. Finally, the diamond micropowder treated with the three coatings was thoroughly mixed.

[0046] like Figure 1 and Figure 2As shown, during assembly, tungsten carbide powder is first thoroughly mixed with a small amount of cobalt powder, and then evenly spread in a metal mold cup 6. This layer is the tungsten carbide alloy base layer 4. A metal mold sheet is then laid on top, followed by a layer of uncoated diamond micro powder 3. The next step is to lay a thoroughly mixed layer of uncoated diamond micro powder and metal double-coated diamond micro powder 2. Finally, a layer of niobium-scandium double-coated diamond micro powder 1, which has undergone two magnetron sputtering coatings, is laid on top. The above mold is then placed into a cavity composed of pyrophyllite blocks 5 and pyrophyllite sheets 7, and pressed into a blank on a column press. After removal, the blank is placed in a graphite mold, and after vacuum reduction treatment for 24 hours, the graphite assembly block is placed back into the pyrophyllite block and assembled in a six-sided top press. The assembly method is as follows. Figure 3 As shown, the sintering oil pressure is 55-60 MPa, the temperature is 1450-1600℃, and the temperature is maintained for 12 minutes after heating. Finally, the processed polycrystalline diamond composite sheet is subjected to ball milling and acid washing to remove the cemented carbide particles mixed in the surface.

[0047] The beneficial effects of this invention are: it can effectively improve the high temperature resistance of PCD, effectively delay the oxidation and graphitization rate of PDC, improve the toughness of PDC, and the PCD prepared by this method can adapt to high-speed and high-impact working conditions, while also being able to withstand greater radial loads, and effectively prevent delamination between the diamond layer and the alloy substrate layer.

[0048] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one" does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0049] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a metal double-coated, high-strength gradient polycrystalline diamond composite sheet, characterized in that: Includes the following steps: 1) Preparation of micro powders for each layer of the composite sheet; Micronized powder cleaning: After acid washing and alkali washing of three different diamond micronized powders, rinse with distilled water 2-3 times; Micronized powder coating: The cleaned diamond micronized powder is placed in a magnetron sputtering coating equipment, and two of the following targets with a purity higher than 99.99% are used to deposit and coat the surface of three different diamond micronized powders with different particle sizes. Obtaining the mixture: Cobalt powder and whiskers are used as sintering agents and mixed with coated diamond micro powder to obtain the mixture; Thoroughly mix the materials: Use a planetary mixer equipped with a vacuum mixing tank to thoroughly mix the materials in a vacuum environment; 2) Obtaining the billet: Particle Laying: Take a metal mold cup (6), mix tungsten carbide powder and a small amount of cobalt powder thoroughly and evenly, and lay them on the inner bottom wall of the metal mold cup (6) as a tungsten carbide alloy base layer (4). Then, lay a metal mold sheet on top of the tungsten carbide alloy base layer (4). Then, lay a layer of uncoated diamond micro powder on top of the metal mold sheet as an uncoated diamond layer (3). The top of the tungsten carbide alloy base layer (4) is fixed by protrusions and grooves. Then, lay a mixture of fully mixed uncoated diamond micro powder and metal double-coated diamond micro powder that has undergone two magnetron sputtering coatings on top of the uncoated diamond layer (3) as a coated diamond and uncoated diamond mixed layer (2). Finally, lay a mixture of double-coated diamond micro powder that has undergone two magnetron sputtering coatings as a coated metal diamond layer (1). Pressing blanks: Place the bottom of the metal mold cup (6) on the top of the pyrophyllite sheet (7), and put the top of the metal mold cup (6) inside the pyrophyllite block (5), so that the metal mold cup (6) is placed inside the cavity composed of the pyrophyllite block (5) and the pyrophyllite sheet (7), and press them into blanks by hydraulic pressure of 25-35MPa on a column press. 3) Obtain the finished product: Blank reduction treatment: Take out the pressed blanks one by one and place them in the cavity of the graphite assembly in the order of pressing the blanks. Reduce the blanks in a vacuum environment for 24 hours. The graphite assembly includes a graphite tube (13). The graphite tube (13) is sleeved on the side of the blank. Graphite sheets (10) are tightly attached to the top and bottom of the graphite tube (13). High-temperature and high-pressure sintering of billet: The reduced billet along with the graphite assembly is placed in the sintering assembly and sintered into a polycrystalline diamond composite sheet under high temperature and high pressure using a six-sided top press. The sintering assembly includes two phosphor iron sheets (12), which are tightly attached to the top and bottom of two graphite sheets (10). Composite conductive plugs (11) are tightly attached to the top and bottom of the two phosphor iron sheets (12). A dolomite tube (9) is sleeved on the side of the graphite tube (13). A second pyrophyllite block (8) is sleeved on the outside of the dolomite tube (9) and the composite conductive plug (11). Finished product: The final product is obtained through ball milling, acid washing, and polishing. The three different particle sizes of the diamond micro powder in step 1) are 1-2μm, 4-8μm, and 30-50μm, respectively. In the mixed material of step 1), the coated diamond micro powder has the following proportions: 1-2 μm diamond micro powder accounts for 5-10 wt.%, 4-8 μm diamond micro powder accounts for 10-15 wt.%, and 30-50 μm diamond micro powder accounts for 75-85 wt.

2. The preparation method according to claim 1, characterized in that, The whiskers in step 1) are one of silicon nitride whiskers, aluminum nitride whiskers, boron nitride whiskers, and zirconium oxide whiskers. The boron nitride whiskers have a length of 30-50 μm and a diameter of 3-5 μm, and the cobalt powder has an average particle size of 10-30 μm and a density of 8.9 g / cm³. 3 .

3. The preparation method according to claim 1, characterized in that, In step 1), the acid washing and alkaline washing are performed by boiling the diamond micro powder in 10 wt.% NaOH and 30 wt.% HNO3 solutions for 30 minutes, respectively.

4. The preparation method according to claim 1, characterized in that, In the mixture obtained in step 1), the mass percentage of cobalt is 5-10 wt.%; the mass percentage of whiskers is 1-5 wt.%; and the mass percentage of diamond micro powder after plating is 85-90 wt.%.

5. The preparation method according to claim 1, characterized in that, In step 1), for diamond micropowders with particle sizes of 1-2 μm, 4-8 μm, and 30-50 μm, the corresponding total coating thicknesses are 0.10-0.15 μm, 0.2-0.3 μm, and 0.3-0.5 μm, respectively. The diamond coating powder is prepared using magnetron sputtering, with two of the following targets selected: high-purity ruthenium, tantalum, niobium, hafnium, technetium, scandium, and vanadium. The chamber vacuum degree is 5 × 10⁻⁶. -3 The sputtering power was 120-180W, the target current was 0.5A, and the working pressure was 0.4Pa. In order to make the diamond powder coating as uniform as possible, the sample stage was continuously oscillated during the coating process. For diamond micro powders with particle sizes of 1-2μm, 4-8μm, and 30-50μm, the corresponding sputtering times were 15min, 30min, and 60min, respectively.

6. The preparation method according to claim 1, characterized in that, In step 2), the Co content in the mixture of tungsten carbide powder and cobalt powder is 16 wt.%.

7. The preparation method according to claim 1, characterized in that, In step 3), the high-temperature and high-pressure six-sided top press has a hydraulic pressure of 55-60 MPa, a temperature of 1450-1600℃, and a sintering time of 5-15 min. The polishing method in step 3) is laser polishing, with a laser power of 6-10MW, a scanning speed of 1000μm / s, and a scanning interval of 10-15μm.

8. A metal double-coated, high-toughness gradient polycrystalline diamond composite sheet prepared according to the preparation method of claim 1, characterized in that: The material includes a tungsten carbide alloy substrate (4), on the top of which an uncoated diamond layer (3) is fixed by means of protrusions and grooves, on the top of which a mixed layer of coated diamond and uncoated diamond (2) is fixed, and on the top of the mixed layer of coated diamond and uncoated diamond (2) is a coated metal diamond layer (1).

Citation Information

Patent Citations

  • Composite material for superhard cutting tool

    CN101591194A

  • Polycrystalline diamond compact with good heat resistance performance and preparation method thereof

    CN111957977A